(untitled) (World Bulletin of Public Health, 2023)
An indicator of the socio-economic development of any country, including Uzbekistan, is the level of development of high-tech medical care. Since the availability of the necessary skills and knowledge in the field of regulatory frameworks, the list of profiles, as well as the timely and competent formation of medical documentation related to high-tech medical care and awareness of medical personnel on organization issues, the referral procedure directly depends on the time of establishing the need for assistance to each specific patient. In this article, based on the questionnaire data, the level of awareness of 130 cardiologists and therapists about high-tech medical care working in various medical institutions of the Samarkand region is analyzed. According to the results of the survey, the awareness of cardiologists and therapists was assessed based on their age, place of work, position, qualification category, work experience, etc. According to the results of the survey, it was noted that 59% of doctors had more than 10 years of work experience and more than 60% of them had a qualification category in their specialty. 58% of doctors had a complete understanding of high-tech medical care, the heads of departments and specialist doctors were the most informed. Among doctors, only 55.8% of the surveyed doctors are well acquainted with the regulatory legal acts regulating the provision of high-tech medical care. At the same time, 2/3 of them noted ambiguity in their interpretation. As a result of this study, it became obvious the full picture of the opinions of doctors on a number of issues related to the development of high-tech medical care, which are necessary for the further formation of the most priority areas that improve the awareness of doctors